Antibacterial Activity Test of a Combination of Ethanol Extract of Bidara Leaf (ziziphus mauritiana) and Betel Leaf (Piper betle L) Against Staphylococcus aureus in Vitro - Nadya Robbani, Azka; Putu Dedy Arjita, I; Sutrisna Wiatma, Deny; Retno Setyowati, Ety (CV. Inara, 2026)
Infections caused by Staphylococcus aureus remain a global health problem, particularly due to increasing antibiotic resistance that limits the effectiveness of conventional therapy. This condition encourages the development of alternative antibacterial agents based on natural materials. Bidara leaves (Ziziphus mauritiana) and betel leaves (Piper betle L.) are known to have antibacterial activity, however the potential of their combination against Staphylococcus aureus has not been widely studied. This study aims to evaluate the antibacterial activity of a combination of ethanol extracts of bidara leaves and betel leaves against the growth of Staphylococcus aureus with three variations of concentration ratios, namely 100%:0%, 50%:50%, and 0%:100%. There are also 2 control groups, namely a positive control using the antibiotic Clindamycin and a negative control using 10% DMSO. The study used a true experimental design with a post-test only control group design and was conducted using an inhibition zone test with the disc diffusion method. In addition, phytochemical screening tests were carried out to identify active compounds in each extract. The results of phytochemical screening of bidara leaf extract, betel leaf extract, and their combination showed positive results containing secondary metabolites in the form of alkaloids, flavonoids, tannins, terpenoids, and phenols. The results showed that the average diameter of the inhibition zones formed were group 1 (100%:0%) 25.6 mm, group 2 (50%:50%) 19.4 mm, and group 3 (0%:100%) 26.2 mm. The Mann-Whitney test showed significant differences between groups (P=0.000), however further tests showed that there were no significant differences between the treatment groups. In conclusion, the combination of bidara leaf (Ziziphus mauritiana) and betel leaf (Piper betle L.) extracts has antibacterial activity against Staphylococcus aureus, but does not show a synergistic effect and is not more effective than single extracts.